Synthesis and carbonic anhydrase inhibitory activities of new thienyl-substituted pyrazoline benzenesulfonamides. (2nd November 2016) - Mete, Ebru; Comez, Birnur; Inci Gul, Halise; Gulcin, Ilhami; Supuran, Claudiu T.
Abstract: A series of new thienyl-substituted pyrazoline benzenesulfonamides were synthesized and their carbonic anhydrase (CA, EC 4.2.1.1) inhibitory activities were tested on the human (h) isoforms hCA I and hCA II. The inhibition constant ( K i ) of these sulfonamides were in the range of 232.16–637.70 nM toward the slow cytosolic isozyme hCA I, and in the range of 342.07–455.80 nM toward hCA II. Many of these compounds showed comparable inhibition with the reference sulfonamide acetazolamide, a clinically used drug. As the sulfonamide CA inhibitors (CAIs) show many therapeutic uses, these derivatives represent interesting examples of a novel class of such derivatives.